2021
DOI: 10.3390/microorganisms9071386
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Microorganisms to Control the Gray Mold of Grapevine: From Screening to Mechanisms

Abstract: In many vineyards around the world, Botrytis cinerea (B. cinerea) causes one of the most serious diseases of aerial grapevine (Vitis vinifera L.) organs. The control of the disease relies mainly on the use of chemical products whose use is increasingly challenged. To develop new sustainable methods to better resist B. cinerea, beneficial bacteria were isolated from vineyard soil. Once screened based on their antimicrobial effect through an in vivo test, two bacterial strains, S3 and S6, were able to restrict t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 103 publications
0
8
0
Order By: Relevance
“…Meanwhile, in other studies with Bacillus ssp. strains, the ability to control gray mold was detected in grape, tomato, and pepper production [ 39 , 40 , 41 ]. In the present study, both traits were well performed by our strain, which is also a B. velezensis , like the strains mentioned above; however, the aforementioned studies did not evaluate the parameters analyzed herein.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, in other studies with Bacillus ssp. strains, the ability to control gray mold was detected in grape, tomato, and pepper production [ 39 , 40 , 41 ]. In the present study, both traits were well performed by our strain, which is also a B. velezensis , like the strains mentioned above; however, the aforementioned studies did not evaluate the parameters analyzed herein.…”
Section: Discussionmentioning
confidence: 99%
“…Among the detrimental factors, the increasing incidence of fungal pathogens that severely affect different perennial organs of the grapevine has become a major concern for farmers and authorities [7][8][9][10][11][12][13][14]. However, most studies were focused on pathogens with immediate impacts on plant productivity, such as downy and powdery mildew [2,15,16], and spoilage fungi affecting grapes and wines, such as Botrytis cinerea (the causal agent of gray mold) [17][18][19], Aspergillus sp., mainly from section Nigri (involved in mycotoxin contamination) [5,13,[20][21][22], and Penicillium spp. (producers of off-flavors) [5,13,18,20,22,23].…”
Section: Introductionmentioning
confidence: 99%
“…Among these, plant growth promoting rhizobacteria are of great interest ( Lugtenberg and Kamilova, 2009 ) since they induce not only stimulation of plant growth but can also protect against pathogens ( Beneduzi et al, 2012 ). Different studies described biological control agents (BCAs) that protect grapevine against gray mold disease ( Abbey et al, 2019 ; Bruisson et al, 2019 ; Esmaeel et al, 2019 , 2020 ; Amarouchi et al, 2021 ; Librizzi et al, 2022 ). Previous work on grapevine in vitro -plantlets demonstrated that Paraburkholderia phytofirmans strain PsJN can protect leaves against Botrytis by a combined effect: defense priming and direct antifungal effect ( Miotto-Vilanova et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%